Cloud Height Measurement System Based on Stereo Vision with Automated Alignment Correction - Carretas, Filipe (2014)
This paper presents the new developments on a stereo vision based cloud base height measurement instrument. The principle of operation will be presented, as well as a description of the current prototype that has been developed. The major improvement presented in this paper consists on the automation of the calibration procedure that compensates for the cameras inherent misalignments. Measurement results are compared with measurements from other instruments.